Designing and Examining the Psychometric Properties OF Effective Factors of Using E-learning Questionnaire in the Elementary Level of Karaj City - mohamad javaheri daneshmand; eghbal zarei; aliakbar sheykhi fini (مطالعات روانشناسی تربیتی, 2018)
The purpose of this study was to design and determine the psychometric characteristics which conducted from the utilization of electronic learning (e-learning) at the elementary level. This research is "quantitative" in terms of nature, is non-experimental type in terms of controlling the variables and in terms of purpose is “applied" one. The research population included all the elementary school teachers in the Karaj city in the 1394-1395 school year with 33000 participants. The sampling method was simple random sampling and the sizes of this sample were restricted by using 295 Cochran sampling formula. First, the original questionnaire was prepared by studying the background research and interviewing specialists and inspiration from similar tools and with 75 questions. A sample of 295 subjects was conducted. Then, the validity of the instrument was corrected by Cronbach's alpha and correlation and cohesion of the questionnaire corrected and edited with the whole test. By using factor analysis, six factors which include organizational factors, information literacy, and technology, educational design, educational resources, environmental factors, motivational factors were determined as the underlying and constituent factors. The specified elements were verified by confirmatory factor analysis. The 45 questions from the total of 75 questions in the primary tool were related to these six factors.